Internet use and aggression in adolescents with attention deficit hyperactivity disorder - Ipci, Melis; Izmir, Sevim Berrin Inci; Ercan, Eyup Sabri (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2019)
Objective: The aim of this study was to investigate the relationship between internet addiction and aggression in adolescents with Attention Deficit Hyperactivity Disorder (ADHD). In addition, we aimed to explore the differences between ADHD subtypes (inattentive type; combination type; hyperactive-impulsive type). Method: The sample consisted of a total of 120 adolescents. The study group included 60 individuals aged between 13 and 17 years (14.70 +/- 2.07) who had presented to a child and adolescent psychiatry clinic and received a diagnosis of ADHD according to the DSM-IV after being interviewed by a specialist, while 60 adolescents without a diagnosis of ADHD made up the control group. Kiddie-Schedule for Affective Disorders and Schizophrenia, present and life time version (K-SADS-PL), Buss-Perry Aggression Questionnaire (BPAQ), Internet Addiction Diagnostic Questionnaire (IADQ), and a semi structured sociodemographic form were used as measurement devices. Results: According to the results of statistical analyses, the ratio of internet addiction and aggression were higher in adolescents with ADHD than in the control group. Especially the rate of internet addiction and aggression was higher in adolescents with ADHD combination type. In addition, there is a positive relationship between internet addiction and aggression in adolescents with ADHD. Conclusion: According to our study results, there is a positive relationship between internet addiction and aggression in adolescents with ADHD. The results of our study will be helpful to develop future protective measures in internet addiction aimed at preventing aggressive behavior of adolescents with ADHD.
Keywords: ADHD; aggression; adolescents; internet addiction